Degradation of oxamic acid using dimensionally stable anodes (DSA) based on a mixture of RuO2 and IrO2 nanoparticles. (July 2020) - Espinoza, L. Carolina; Sepúlveda, Pamela; García, Alejandra; Martins de Godoi, Denis; Salazar, Ricardo
Abstract: Dimensionally stable anodes (DSA) have been widely used to degrade organic compounds because these surfaces promote the electrogeneration of active chlorine species in the bulk of the solution, as well as in the vicinity of the anode when NaCl is used as supporting electrolyte. In this work, the nanoparticles synthesis of IrO2 and RuO2 was performed to obtain two types of DSA electrodes named Class I and II to degrade oxamic acid. For Class I and II DSA, the nanoparticles used were synthesized separately and in the same reaction medium, respectively. Electrolysis were carried out in an open cylindrical cell without division at 25 °C, DSAs were used as anodes and a stainless-steel electrode as cathode, both elements have a geometric area of 2.8 cm 2 immersed in 0.05 mol L −1 of NaCl or Na2 SO4 and a current density of 3 mA cm −2 was applied for 6 h. Active chlorine species generated in the absence of oxamic acid in NaCl were also detected and quantified through ion chromatography. In Na2 SO4 there was no degradation of the compound, but in NaCl the oxamic acid concentration reaching 85% with Class I DSA. The same tendency is observed in mineralization, in which Class I DSA allowed reaching a CO2 transformation close to 73%. The difference in the results occurs because with Class I DSA, more hypochlorite is generated than with Class II and therefore there is a larger amount of oxidizing species in the solution that enables the degradation and mineralization of oxamic acid. Graphical abstract: Image 1 Highlights: DSA-type electrodes of Ru and Ir oxides were prepared to treat oxamic acid. Concentration and type of active chlorine species generated could depends on the type of oxide. Oxamic acid was not removed in Na2 SO4 using DSA-type electrodes. Oxamic acid was mineralized using DSA-type electrodes in NaCl Class I DSA-type electrodes showed higher percentages of mineralization than Class II.